A comparative study of viscoelastic models for ocean wave dissipation in ice-covered regions of the eastern Canadian shelf. (1st July 2021) - Lin, Shangfei; Sheng, Jinyu; Xing, Jiuxing
Abstract: A nested-grid ocean surface wave model based on WAVEWATCH III (WW3) is used to investigate wave propagations in the ice-covered regions of the eastern Canadian shelf (ECS) during a winter storm in March 2014. The applicability of two viscoelastic models (known as IC3 and IC5) for wave dissipation in ice is investigated. Two essential ice rheological parameters (kinetic viscosity v and elasticity G ) in these two viscoelastic models are determined by comparing the simulated significant wave heights (SWHs) with observations from altimeters and buoys. Both viscoelastic models reproduce reasonably well the observed wave propagations in ice with the average scatter index less than 12.5% for the SWHs near the ice edge. In the inner ice pack, however, IC3 is superior to IC5, since IC5 produces unrealistic large waves. The two viscoelastic models perform differently in the inner ice pack, due largely to the nonlinear effect of different wave dissipation rates on the wind input for surface waves. In comparison with IC5, IC3 has a stronger dependence of the wave dissipation rate on the wave frequency and thus generates more rapidly wave energy decay in ice. Wave scattering, which is typically not considered in many previous studies, significantly modifies wave propagations in ice over the ECS during the study period. Wave scattering leads to large decreases of SWHs and increases of mean wave periods in the inner ice pack due to the nonlinear effect on the wind input associated with broadening of wave directional spreads. Highlights: First application of viscoelastic models for wave dissipation in ice over the eastern Canadian shelf. A comparative study of different viscoelastic models for wave dissipation in ice. Identifying the important role of wave scattering in ice over the eastern Canadian shelf.